THEORETICAL AND METHODOLOGICAL ANALYSIS OF SCIENTIFIC APPROACHES TO DEFINING THE CATEGORIES OF «LEISURE» AND «EVENT» IN THE CONTEXT OF TOURIST AND RECREATIONAL ACTIVITIES (Development Service Industry Management, 2025)
The article explores theoretical and methodological approaches to the concepts of “leisure” and “event” within the broader framework of tourism and recreational activities. The study presents an in-depth analysis of classical and contemporary theories from renowned scholars such as T. Parsons, J. Huizinga, and S. Freud. These concepts are investigated through sociological, psychological, and cultural lenses, allowing for a multidimensional understanding of leisure as a form of human activity. Leisure is defined not merely as time free from work or obligations, but as a vital sociocultural phenomenon that facilitates personal growth, the development of identity, socialization, and cultural enrichment. Furthermore, the article examines the evolution of event studies as a separate scientific field and emphasizes the growing importance of event management in tourism and recreational planning. Events are conceptualized as both planned activities and socio-cultural catalysts that have the potential to attract tourists, stimulate local economies, and foster civic pride. Particular emphasis is placed on the role of events in territorial branding and in shaping a region’s touristic appeal. The research also highlights the synergistic relationship between leisure and events as complementary domains that together enhance the quality and diversity of tourist experiences. By classifying various types of events—cultural, entertainment, business, and recreational—the study offers a systematic approach to understanding their potential in achieving sustainable tourism goals. The article concludes that a deep theoretical understanding of leisure and events contributes significantly to effective strategic planning and policy-making in the tourism and recreation sectors. Overall, the work contributes to the broader discourse on how leisure and events function as dynamic instruments in contemporary sociocultural transformation processes, particularly in the context of global tourism trends.
Keywords: leisure; event; tourism; recreation; event management; events; cultural practices; tourist space